Understanding Jonathan Edwards : an introduction to America's theologian - McDermott, Gerald R. (Gerald Robert) (Oxford scholarship online., 2009)
This title is an introduction to Jonathan Edwards (1703-58). It looks at subjects which Edwards considered vitally important such as revival, Bible, typology, aesthetics, literature and preaching, philosophy and world religions.